PERAN KOMUNITAS MEREK DAN KETERLIBATAN KOMUNITAS DALAM MEMBANGUN KEPERCAYAAN MEREK DI MEDIA SOSIAL - Dhani Besari; Lukman Hakim (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
This study aims to analyze the role of brand communities and community involvement in building brand trust in social media. The type of method used in this research is a quantitative method with 153 respondents, the sampling technique in this study is nonprobability sampling technique with purposive sampling method, the data used is primary data obtained through respondents' answers using a type of interview or closed questionnaire. The intended respondents were members of the brand community from the RUBY Community by PT AVO Innovation Technology (AVO) with 153 respondents. The data analysis technique used in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. PLS-SEM analysis consists of two Outer model and Inner model. The results of this study indicate that brand community and community involvement have a positive and significant effect on brand trust in social media.